Closer and further away – emergency-remote teacher education, orientations and student-bodie - Emilia Åkesson; Edyta Just; Katarina Eriksson Barajas (Högre Utbildning, 2022)
This paper contributes knowledge on the effects of materiality and space on teaching and equal access to teacher education. Through an intersectional analysis, with a specific focus on orientations, bodies and materiality, we show how student-bodies orientate closer to or further from various parts of teacher education as an effect of the materiality of emergencyremote vs. on-campus education. We elaborate on three different student-body orientating processes that take place during teacher education. These are all related to the emergencyremote education implemented as a consequence of the COVID-19 pandemic. We call these processes ‘remote education as relief’, ‘the embodiedness of raising the hand on Zoom’ and ‘energy-draining pre-recorded lectures’. We show how the materiality of emergency-remote education orientates the participants situated within the bodily horizons of intersectional positions of being deaf, female, racialized as non-white and not having Swedish as a first language, both closer to and further away from various parts of their teacher education. The analysis is based on both individual and group interviews with twelve teacher students. The paper contributes insights to emergency-remote education, remote education and on-campus educating.